Herb5GluCon: A novel polyherbal formulation with dual-action inhibiting properties against oxidative stress and glycoside hydrolases – an in silico and in vitro approach - Abbirami Balachandran; Patrick N. Okechukwu; Baskaran Gunasekaran; Jeleń Małgorzata; Beata Morak-Młodawska; Gabriele R.A. Froemming; Sameer Sapra; Charlie A. Lavilla, Jr.; Merell P. Billacura; Salini D. Rajendran; Anis Najwa Abdul Rani; Anand Gaurav (Phytomedicine Plus)
Introduction: Oxidative stress contributes to hyperglycaemia by inducing the hyperactivity of alpha-amylase (AA) and alpha-glucosidase (AG) enzymes. The study aimed to evaluate the antioxidant and anti-glycoside hydrolase potential of a novel polyherbal formulation (Herb5GluCon) and identify its phytoconstituents. Methods: The in silico molecular docking of the compounds were performed using AutoDock Vina 1.2.0. The in vitro antioxidant activity of Herb5GluCon was evaluated using chemical assays and cellular ROS determination assay while AA and AG inhibition assays were performed to evaluate its in vitro anti-glycoside hydrolase activity. The bioactive compounds present in Herb5GluCon was identified using high-resolution mass spectrometry (HRMS) and these compounds were subjected to ADME analysis using the SwissADME, pkCSM and SwissTargetPrediction servers. Results: All compounds showed strong binding energies to AA and AG. The antioxidant assays revealed a strong radical-scavenging property of Herb5GluCon with strong IC50 values, respectively. Similarly, the enzyme inhibition assays also proved the potent inhibitory effect of Herb5GluCon with strong IC50 values. The HRMS identified 20 compounds to which, the ADME profiling of all compounds revealed high drug-likeness profiles with a strong target interaction to enzymes including AA and AG. Conclusion: Herb5GluCon showed promising in vitro antioxidant and anti-glycoside hydrolase activities which served as a basis of understanding to conduct further research of evaluating the therapeutic potential of Herb5GluCon and its phytoconstituents in the treatment of diabetes and its associated complications.